Rethinking Basic Infrastructure: French Aid and Metro Development in Postwar Latin America - Chastain, Andra B. (Comparativ, 2020)
Postwar Latin America witnessed a remarkable wave of metro construction as eight new urban rail transit systems opened in Mexico, Brazil, Chile, and Venezuela in a span of less than twenty years. What explains this dramatic transformation in the built environment of Latin American cities? This article argues that French metro boosters played a crucial role in the Latin American transit boom between the 1960s and the 1980s. While international development agencies favoured what they considered more basic infrastructure projects such as ports or dams, France constituted a key source of aid for modernizing urban planners in Latin America. Relationships between Latin American planners and French funders benefitted French manufacturing interests, in addition to Latin American metro proponents. This article draws on sources in Spanish, Portuguese, and French, including archival sources from the French Company for the Design and Construction of Urban Transport (Société française d’études et de realizations de transports urbains, SOFRETU), local news articles, and official reports by Latin American metro agencies. It highlights the role of bilateral aid between France and Latin America, thus complementing work on multilateral organizations and US influence in the region.